Discretionary disclosures using a certifier - Marinovic, Iván; Sridhar, Sri S. (Journal of Accounting and Economics, 2015)
This paper studies two disclosure regimes when a firm with superior private information must rely on a strategic certifier to disclose credibly its prospects. In the ex ante (ex post) disclosure regime, the firm must decide on whether to hire the certifier before (after) observing the certifier׳s noisy assessment. Endogenously determined certification fees can actually cause the disclosure probability to decrease in disclosure precision. In the ex ante regime, favorable disclosures are more informative than unfavorable disclosures because of additional positive signaling effect. In the ex post (ex ante) regime, the certifier has incentives to increase (decrease) the disclosure precision.